Tridimensional assessment of the mandibular angle in patients with different skeletal patterns by cone-beam computed tomography scans: a retrospective study - Murilo Miranda-Viana; Gabriel Mosso Moreira; Larissa Moreira de Souza; Yuri Nejaim; Francisco Haiter-Neto; Deborah Queiroz Freitas (BMC, 2023)
Abstract Background Since the muscles of chewing are involved in the region of the mandibular angle, important structures in surgical and orthodontic procedures, to study its morphological aspects and the possible influence of different patterns of skeletal development would be of interest. Thus, this study aimed to assess the influence of patient characteristics - such as sex, skeletal malocclusion (Class I, Class II, and Class III) and facial type (brachycephalic, mesocephalic, and dolichocephalic) - on the width, height, thickness, and volume of the mandibular angle, using cone-beam computed tomography (CBCT) scans. Methods CBCT scans were assessed − 144 men and 154 women, total of 298 - and classified according to skeletal patterns (skeletal malocclusions and facial types). Width, height, and thickness of the mandibular angle were measured using OnDemand 3D software. The volumetric measures of the mandibular angle were obtained using the ITK-SNAP software. Analysis of Variance (multiway ANOVA) with Tukey's post-hoc test compared the data, with a 5% significance level. Results Among the factors studied, sex significantly influenced all the analyzed variables (height, width, thickness, and volume of the mandibular angle) (p < 0.05); in general, male individuals presented higher values than females. In some cases, the skeletal malocclusion and facial type factors influenced only the width and height variables (p < 0.05); in general, the Class III and dolichocephalic individuals presented higher values in relation to the other types of skeletal malocclusions and facial types. Conclusions Variations in the craniofacial growth pattern, considering the different skeletal malocclusions and facial types, had some influence in the width and height dimensions of the mandibular angle. Furthermore, sex influenced all the studied variables.